Establishment of an efficient Agrobacterium-mediated Genetic Transformation protocol for Potato (Solanum tuberosum L.) var. Diamant - Mollika, Sanjida Rahman; Islam, Tahmina; Hoque , M I; Sarker, R H (Plant Tissue Culture and Biotechnology, 2025)
The experiment aimed to standardize the transformation capability of leaf disc, internode, and nodal segment explants from the Diamant variety of potato (Solanum tuberosum L.). Nodal segments, internodes and leaf disc explants were infected with Agrobacterium tumefaciens strain LBA4404, which harbors the binary vector pBI121 containing the GUS reporter gene and the neomycin phosphotransferase (NPTII) kanamycin resistance gene. Optimal transformation responses were observed in nodal segments with a bacterial suspension exhibiting an optical density of 0.6 at 600 nm in the Diamant variety. Furthermore, a 30 min incubation followed by 72 hrs of co-cultivation was identified as the most successful method for transformation, as indicated by the transient GUS histochemical assay. Transformed shoots were selected utilizing MS medium with 4.0 mg/l BAP, 1.0 mg/l IAA, 0.5 mg/l GA3, 300 mg/l carbenicillin and 200 mg/l kanamycin. The stable integration of GUS and NPTII genes was validated using PCR analysis utilizing genomic DNA extracted from transformed plants. Plant Tissue Cult. & Biotech. 35(1): 209-218, 2025 (June)